Regional Cooperation in Seed Sector: Learning Visit - International Potato Center; CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The learning visit aimed to meet and learn from the government officials in Bangladesh and India who have been advocating the better utilization of regional cooperation in seed sector to strengthen food and nutrition security in the South and Southeast Asian Regions.